Making Sense of Statistics : - Wood, Michael (Palgave McMillan, 2003)
"Making Sense of Statistics" provides a thorough but accessible introduction to statistics and probability, without the distractions of mathematics. The book has no algebraic formulae or equations, but it does explain how and why methods work and exactly what answers mean. Guidance is provided on how to design investigations, analyse data and interpret results. There are exercises and case studies from a variety of areas of application, and an accompanying website from which interactive spreadsheet models and data files can be downloaded.